Website Redesign of Bandung City Special Dental and Oral Hospital - Sophia Purbasari; Mohammad Manzili Kurnia (Medicor : Journal of Health Informatics and Health Policy, 2026)
This study examines the redesign of the Bandung City Special Dental and Oral Hospital (RSKGM) website to address usability and accessibility issues in public healthcare digital platforms. As digital health services have become increasingly essential, particularly after the COVID-19 pandemic, hospitals are expected to provide efficient, user-friendly, and integrated online systems. The existing RSKGM website presented several UI/UX weaknesses, such as the separation of registration and information pages and poorly designed call-to-action buttons, which hindered the user experience. Using a qualitative approach supported by interviews, observations, questionnaires, and literature review, the research applied the 5W+1H and SWOT analytical frameworks, followed by wireframing, prototyping, and usability testing. Results showed that 69.6% of users found the previous website unattractive and difficult to use, while 85.7% agreed it needed a redesign. The new website successfully integrated registration and information services, improved call-to-action clarity, and reduced registration time from 15 seconds to 1.5 seconds. The novelty of this study lies in its integration of User-Centered Design (UCD) and the AISAS communication model to develop a contextual framework for redesigning digital health services in public hospitals, offering a new approach that bridges usability, communication strategy, and institutional branding. The findings demonstrate how user-centered redesign can enhance efficiency, accessibility, and user satisfaction while providing practical implications for digital transformation in public healthcare institutions.